The effects of an acute Tai Chi on emotional memory and prefrontal cortex activation: a fNIRS study - Wang, Haining; Guo, Yujiang; Fan, Hao; Chen, Zhihao; Liu, Shumeng; Zhao, Longfei; Shi, Yonggang (Frontiers in Behavioral Neuroscience, 2025)
ObjectiveAcute exercise has the potential to influence emotional memory and cortical hemodynamics, but the specific effects depend on the type of exercise. This study aimed to determine whether acute Tai Chi practice enhances emotional memory and prefrontal cortex activation compared to cycling and a control condition.MethodsUsing a within-subjects crossover design, 36 healthy university students completed three interventions: Tai Chi, cycling, and a resting control condition. Emotional memory performance was assessed before and after each intervention, and cortical hemodynamics were measured using functional near-infrared spectroscopy (fNIRS). The correlation between oxyhemoglobin (Oxy-Hb) concentration in the prefrontal cortex and emotional memory accuracy was analyzed.ResultsCompared to cycling and the control group, the Tai Chi intervention showed: (1) a significantly higher accuracy of positive emotional memory; (2) a greater increase in Oxy-Hb concentration in the left dorsolateral prefrontal cortex (L-DLPFC) during positive emotional memory tasks; (3) a stronger positive correlation between Oxy-Hb concentration in the L-DLPFC and emotional memory accuracy. In contrast, cycling improved positive emotional memory accuracy to a lesser extent, while the control group showed no significant changes.ConclusionTai Chi, compared to cycling and rest, significantly enhanced positive emotional memory and L-DLPFC activation. These findings highlight the unique potential of Tai Chi to improve emotional memory through increased cortical activation, suggesting its effectiveness as a cognitive-emotional intervention.